ENHANCING ENTREPRENEURSHIP DEVELOPMENT PROGRAMMES IN SWAZILAND - BUKUTU, JOHN J. F. (My University, 2011)
It is increasingly being accepted that entrepreneurship support offers a new model for poverty alleviation and the ensuring of job creation and economic growth. There is also an observable causal relationship between entrepreneurship, the support thereof, economic development and poverty alleviation. The impact of entrepreneurship support and growth is and would be greater in developing countries like Swaziland. This study explores how entrepreneurship support initiatives can be enhanced in Swaziland, during this momentous period for entrepreneurship in Swaziland. Entrepreneurship support is an emerging concept in Swaziland, characterized by the increasing emphasis on small and medium enterprises development by the government. Entrepreneurship development programmes and initiatives can be an effective tool to add to this policy direction of the government. However, unless these programmes achieve their stated objectives of developing the Swazi entrepreneur, there will be continued wasteful commitment of resources. This report explores ways and means that can be applied to enhance entrepreneurship development programmes and initiatives in Swaziland. This was done through a qualitative research, which employs a case study approach. The findings of this study are quite instructive. They reveal that there are factors that are critical to the support for entrepreneurship. This is important, particularly in the case of Swaziland, where entrepreneur support programmes are an emerging concept. The findings also have implications for the theoretical understanding of the relationship between successful entrepreneurship and external support. Most of the literature reviewed during the study has quite a lot on the internal characteristics of entrepreneurs and the success or failure of their enterprises. It is hoped that this study will contribute to the dialogue between the view that entrepreneurial success is informed by the internal characteristics of the ii entrepreneur and that external nurturing and support leads to entrepreneurial success.
MM thesis - P&DM
Keywords: Entrepreneurship, Swaziland